URGENSI KLAUSULA RAHASIA DAGANG DALAM KONTRAK KERJA ANTARA KARYAWAN DENGAN PERUSAHAAN (Studi Pada Kentucky Fried Chicken Kota Pekanbaru) - AHMAD IRFAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. Jelly Leviza, SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHum A trade secret owner has to keep important information confidential from other parties that can harm his importance. The Law on Trade Secrets explains that the owners of trade secrets have managed to keep their trade secrets if they have taken decent and proper steps, as such a company that has standard procedures based on general practices applicable in other places and or written in internal provisions of the company. The research discusses about the contract of Kentucky Fried Chicken and their employee named Mr. X written in form of an employment contract dated August 18, 2018, stating that “Employees are obliged to keep the confidentiality of the managerial system and restaurant managerial methods obtained during their years of service in the company and after their contract is terminated”. In practice, Mr. X, as a former employee of Kentucky Fried Chicken, has now established his own business named RG Fried Chicken on Jalan Diponegoro in Pekanbaru.Keywords: Trade Secrets, Settlement of Dispute over Trade Secrets.